Measurement and control basics - Hughes, Thomas A. (International Society of Automation (ISA), 2015)
A comprehensive treatment of the basic principles of process control and instrumentation, for engineers, technicians, management, and sales personnel new to the subject. After a review of relevant mathematics, chapters cover electrical, electronic, and digital fundamentals, process control computers, final control elements, and methods and instruments for measuring factors such as pressure, level, and flow. Includes chapter introductions and exercises. Appendices offer standard graphics symbols and thermocouple tables.